A case of reinfection with a different variant of SARS-CoV-2: case report - Nagashige Shimada; Masahiro Shinoda; Hiroaki Takei; Yuto Yoshida; Masashi Nishimura; Mio Kousaka; Miwa Morikawa; Takashi Sato; Hiroto Matsuse; Masaharu Shinkai (SpringerOpen, 2023)
Abstract Background Coronavirus disease 2019 (COVID-19) was previously thought to have a low reinfection rate, but there are concerns that the reinfection rate will increase with the emergence and spread of mutant variants. This report describes the case of a 36-year-old, non-immunosuppressed man who was infected twice by two different variants of COVID-19 within a relatively short period. Case presentation A 36-year-old Japanese man with no comorbidities was infected with the E484K variant (R.1 lineage) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Symptoms were mild and improved with symptomatic treatment alone. About four months later he presented to another outpatient department with high fever and headache. We diagnosed him as infected with the Alpha variant (B.1.1.7) of SARS-CoV-2 based on SARS-CoV-2 real-time reverse transcription polymerase chain reaction testing (RT-PCR). The patient was hospitalized with high fever. The patient received treatment in the form of anti-inflammatory therapy with corticosteroid and antibacterial chemotherapy. The patient improved without developing severe disease. Conclusion Concerns have been raised that the reinfection rate of COVID-19 will increase with the emergence of mutant variants. Particularly in mild cases, adequate amounts of neutralizing antibodies may not be produced, and reinfection may thus occur. Continued attention to sufficient infection control is thus essential.